Chemical reactivity in quantum mechanics and information theory - Nalewajski, R. F. (Roman F.) (Elsevier, 2023)
Chemical Reactivity in Quantum Mechanics and Information Theory introduces a thermodynamic-like description of molecular systems and provides an objective treatment of their fragments. The book formulates adequate entropic tools for probing in chemical terms and the electronic structure of molecules and rationalizing reactivity principles. It covers the information origins of chemical bonds, covalent/ionic composition, trends in molecular stability and reactivity, equilibrium polarizations and charge-transfer reconstructions of reactive complexes, as well as the phase/current promotions of molecular substrates. In addition, the book introduces a precise descriptor of molecular fragments and clarifies mostly intuitive semantics of several chemical concepts. Readers will find a precise and unbiased description of chemical reactivity phenomena in Donor-Acceptor systems in terms of quantum states and generalized concepts of Information/Communication theories.